Oil mists and vapours: A review of exposure and toxicity, with dose descriptors from inhalation studies - Niels Hadrup; Jorid B. Sørli; Marie Frederiksen; Anoop K. Sharma; Sabine Kafert-Kasting; Sven Schuchardt; Annette Bitsch; Per A. Clausen; Anne Thoustrup Saber; Ulla Vogel; Karin S. Hougaard (Toxicology, 2026)

Neck extensor myopathy- a treatable cause of dropped head syndrome - Nibu Varghese; Vimal Chandraghosh K D; Deepak Menon; Abdurahiman P; Anoop Kattadimmal; Jubin Mathew; Shobika B S; Nyla Mary Babu (Acta Neurologica Belgica, 2024)

Pattern and drivers of danaine butterfly migration in Southern India: implications for conservation - P. A. Vinayan; M. A. Yathumon; N. S. Sujin; B. N. Anjan Kumar; P. A. Ajayan; P. K. Muneer; N. M. Vishnu; C. S. Anwar; N. R. Anoop (Journal of Insect Conservation, 2023)

Capsule Network–based architectures for the segmentation of sub-retinal serous fluid in optical coherence tomography images of central serous chorioretinopathy - S. J. Pawan; Rahul Sankar; Anubhav Jain; Mahir Jain; D. V. Darshan; B. N. Anoop; Abhishek R. Kothari; M. Venkatesan; Jeny Rajan (Medical & Biological Engineering & Computing, 2021)

Gene-based SNP discovery and genetic mapping in pea - Anoop Sindhu; Larissa Ramsay; Lacey-Anne Sanderson; Robert Stonehouse; Rong Li; Janet Condie; Arun S. K. Shunmugam; Yong Liu; Ambuj B. Jha; Marwan Diapari; Judith Burstin; Gregoire Aubert; et al. (Theoretical and Applied Genetics, 2014)

P alaeoenvironmental implications of evaporative gaylussite crystals from Lonar Lake, central India - A. ANOOP; S. PRASAD; B. PLESSEN; N. BASAVAIAH; B. GAYE; R. NAUMANN; P. MENZEL; S. WEISE; A. BRAUER (Journal of Quaternary Science, 2013)
We have undertaken petrographic, mineralogical, geochemical and isotopic investigations on carbonate minerals found within a 10‐m‐long core from Lonar Lake, central India, with the aim of evaluating their potential as palaeoenvironmental proxies. The core encompasses the entire Holocene and is the first well‐dated high‐resolution record from central India. While calcite and/or aragonite were found throughout the core, the mineral gaylussite was found only in two specific intervals (4630–3890 and 2040–560 cal a BP). Hydrochemical and isotope data from inflowing streams and lake waters indicate that evaporitic processes play a dominant role in the precipitation of carbonates within this lake. Isotopic (δ 18 O and δ 13 C) studies on the evaporative gaylussite crystals and residual bulk carbonates (calcite) from the long core show that evaporation is the major control on δ 18 O enrichment in both the minerals. However, in case of δ 13 C additional mechanisms, for example methanogenesis (gaylussite) and phytoplankton productivity (calcium carbonate), play an additional important role in some intervals. We also discuss the relevance of our investigation for palaeoclimate reconstruction and late Holocene monsoon variability. Copyright © 2013 John Wiley & Sons, Ltd.

Genetic characterization of 2006–2008 isolates of Chikungunya virus from Kerala, South India, by whole genome sequence analysis - E. Sreekumar; Aneesh Issac; Sajith Nair; Ramkumar Hariharan; M. B. Janki; D. S. Arathy; R. Regu; Thomas Mathew; M. Anoop; K. P. Niyas; M. R. Pillai (Virus Genes, 2010)